2017
DOI: 10.1182/bloodadvances.2017004903
|View full text |Cite
|
Sign up to set email alerts
|

Engraftment of chronic myelomonocytic leukemia cells in immunocompromised mice supports disease dependency on cytokines

Abstract: Key Points Transgenic mice expressing 3 human cytokines enable expansion of CMML cells with limited stem cell engraftment. The mutational profile of CMML cells that expand in mice mirrors that of patient monocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 17 publications
1
17
0
Order By: Relevance
“…Some patient samples that failed to engraft NSG mice yielded significant grafts in NSGS mice, demonstrating a strict dependence of a subset of these samples on myeloid cytokine signals and revealing an increased sensitivity for human AML leukemic initiating cells, consistent with the previous finding that exogenous cytokines can aid CD34+ engraftment when low cell numbers are infused [17]. Similar results have also recently been reported for MDS, CMML, and JMML [1820], indicating a benefit of SGM3 expression for a broad range of myeloid neoplasms.…”
Section: Introductionsupporting
confidence: 85%
“…Some patient samples that failed to engraft NSG mice yielded significant grafts in NSGS mice, demonstrating a strict dependence of a subset of these samples on myeloid cytokine signals and revealing an increased sensitivity for human AML leukemic initiating cells, consistent with the previous finding that exogenous cytokines can aid CD34+ engraftment when low cell numbers are infused [17]. Similar results have also recently been reported for MDS, CMML, and JMML [1820], indicating a benefit of SGM3 expression for a broad range of myeloid neoplasms.…”
Section: Introductionsupporting
confidence: 85%
“…Immunohistostaining of human CD45 revealed the presence of human CD45 + blood cells, particularly around the small blood vessels in the teratomas. It was recently reported that primary samples of CMML and JMML can be transplanted into NSGS mice that trans-genetically express human GM-CSF, interleukin-3, and stem cell factor to develop remarkably humanized mouse models 21 23 . Our particular technique of developing humanized CMML mouse models using CMML-iPSCs offers an alternative approach that boasts an added advantage: because CMML-iPSCs can be used repeatedly, the mouse models can be produced in infinitely large quantities with limited initial resources.…”
Section: Discussionmentioning
confidence: 99%
“…21 During the last decade, several laboratories have published a number of complementary approaches for the generation of MDS PDX. [22][23][24][25][26][27][28][29][30][31][32][33][34] Importantly, these combined efforts have demonstrated the engraftment capacity of most MDS subtypes, [23][24][25][26][27][28]34 that the expanded cells retain the genetic and phenotypic features of the primary tumor, [24][25][26][27]29,30,32,34 that these PDX models also sustain engraftment in secondary recipients 24,27,29,34 and that they allow evaluation of new therapies. 32,33 Nevertheless, as summarized in Table 1 and Figure 1, these models are quite heterogeneous.…”
Section: The History Of Myelodysplastic Syndrome Patient-derived Xenomentioning
confidence: 99%
“…The most commonly used recipient for the generation of PDX is the NSG strain which harbors mutations in Prkdc and Il2g leading to the absence of B, T and NK cells. 35 The constitutive expression of the human cytokines interleukin-3 (Il-3), granulocyte-macrophage colony-stimulating factor (GM-CSF) and stem cell factor (SCF) on this background (NSG-S, also designated NSG-SGM3) does not lead to enhanced engraftment of most MDS subtypes, except for chronic myelomonocytic leukemia, 28 in contrast to the situation in AML. 24,26,29,36 On the other hand, the recently developed MISTRG strain, expressing human macrophage colony-stimulating factor (M-CSF), IL-3, GM-CSF, signal regulatory protein alpha (SIRPα) and thrombopoietin at physiological levels on a different immunodeficient background (Rag2 -/-, IL2Rg -/-), was recently demonstrated to be a promising host for engraftment of MDS patients' material.…”
Section: The History Of Myelodysplastic Syndrome Patient-derived Xenomentioning
confidence: 99%